Dwujęzyczność szlachty na przykładzie XVIII -wiecznej sylwy = Bilingualism of the nobility community: An analysis of the eighteenth-century "silva rerum" - Szagun, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article discusses Polish-Latin bilingualism as a distinctive feature of the nobility (also known as "the Sarmatians"). Sarmatism is characterized by the type of communication that is marked by deeply assimilated Latin or so-called "macaronic speech". The tendency towards macaronisation is seen as an exponent of the aesthetic Sarmatian erudition rather than as a symptom of the degeneration of the Polish language during the Saxon times.
Keywords: dwujęzyczność; bilingwizm; elita; elitarny; język; łacina; polszczyzna; makaronizowanie; socjolekt szlachecki; sylwa; wspólnota szlachecka; tożsamość; bilingualism; elite; exclusive; language; Latin; macaronisation; Polish language; sociolect of the nobility; "silva rerum"; noble community; identity